2009
DOI: 10.1071/py08065
|View full text |Cite
|
Sign up to set email alerts
|

Better than nothing? Restrictions and realities of enhanced primary care for allied health practitioners

Abstract: Participation of allied health professionals (AHP) in the Enhanced Primary Care (EPC) program is increasing. However, access to allied health services is strictly delineated under the EPC program and AHP face unique practice realities in providing care to patients with chronic conditions. This paper examines the discretionary practices adopted by AHP in response to the realities at the policy-practice interface and situates the discussion within a description of their experiences with EPC. Semistructured telep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…Research examining allied health perspectives of EPC and CDM items indicates team care is more a paper exercise than a reality, with allied health providers reporting poor liaison and linkages with GPs. 11 The key mechanisms for facilitating team care are the Multidisciplinary Care Plan and the Case Conference items. 6 There is evidence to suggest that in some cases GPs are less inclined to participate in case conferences compared to health assessments and GP Management Plans.…”
Section: Introductionmentioning
confidence: 99%
“…Research examining allied health perspectives of EPC and CDM items indicates team care is more a paper exercise than a reality, with allied health providers reporting poor liaison and linkages with GPs. 11 The key mechanisms for facilitating team care are the Multidisciplinary Care Plan and the Case Conference items. 6 There is evidence to suggest that in some cases GPs are less inclined to participate in case conferences compared to health assessments and GP Management Plans.…”
Section: Introductionmentioning
confidence: 99%
“…After a decade of operation, few studies have evaluated the CDM program. Early descriptive studies reported a lack of collaboration and communication between health professionals, particularly between general practices and allied health providers . There was recognition of a need to encourage GPs to engage with the program's team‐based management approach to patient care, which differs from the traditional model of independent care provided by GPs .…”
Section: Introductionmentioning
confidence: 99%
“…Patient uptake of individual dietetics consultations increased threefold from 2005 (64 000 services) to 2010 (205 000 services). However, in 2010 the utilisation of services across all allied health professions varied widely by geographic region, suggesting that patients' access to local services may not be adequate across all areas of Australia . For example, a NSW case study of six rural general practices observed that dietetics consultations were provided at approximately half the average rate for NSW in 2005–2006 and in 2006–2007 …”
Section: Introductionmentioning
confidence: 99%
“…Australian dietitians report to restrict consultation frequency and length due to insufficient funding under the Australian Medicare scheme [4,8]. Such 'abbreviated care' is of concern for patient health outcomes [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Primary healthcare professionals, including dietitians, report challenges in providing effective care due to time and financial constraints under profession-specific requirements [4][5][6][7]. Australian dietitians report to restrict consultation frequency and length due to insufficient funding under the Australian Medicare scheme [4,8].…”
Section: Introductionmentioning
confidence: 99%